The Relationship between German Literature and German Linguistics Today and Yesterday. A Suggestion for the Teaching of German as a Foreign Language in German Study Programs at the University Level - Foschi Albert, Marina (Glottodidactica, 2015)
In recent years, the “crisis of German studies” has become an increasingly current topic within academic discourse. This SUBJECT, more precisely defined as “legitimation crisis of traditional German studies”, has been long debated in Germany. Legitimation is a common principle in the fields of law, political science, and sociology. It refers to other principles such as ‘legitimity’ and ,justification’. Since the Nineties, the crisis in German literature studies appears to be rather an identity crisis, the origin of which can be seen in the centrifugal forces of attraction of several other disciplinary approaches. Something similar has happened – worldwide – in the field of German linguistics, and even in the branch of German as a Foreign Language teaching practice, due to the progressively increasing habit of providing the GFL-object with attributes specifying its specific purposes, for instance: German for Occupational Purposes, German for Business, German for Medical Purposes, for legal Professionals, Engineers, German for young, adult, senior learners etc. The question of which variety of German should be considered at the university level depends upon several factors, a simple answer is therefore not forthcoming. It is extremely important for the modern field of German studies especially within the “German as a Foreign Languagecountries”, that the object „GFL for humanistic purposes” be clearly defined, at least as a variety within the multiplicity of given alternatives.